Kebijakan Komunikasi Perpustakaan Kabupaten Siak Melalui Program Transformasi Perpustakaan Berbasis Inklusi Sosial untuk Pemberdayaan Masyarakat - Yazid, Tantri; Iskandar, Dahrial; Salam, Noor Efni; Elsarena, Mai Sela Rosa (Laboratorium Jurusan Ilmu Pemerintahan FISIP Universitas Riau, 2024)
The current transformation of public libraries is a social inclusion-based library transformation that not only maintains the sustainability and existence of libraries, but also directs them to be part of achieving Sustainable Development Goals (SDG's), which is a sustainable development program that is aligned with the mission of the United Nations (UN) through a joint development resolution plan until 2030. This is what makes public libraries and village libraries to help the Indonesian government program in accelerating poverty alleviation. This study aims to analyze “How is the Communication Strategy of the Siak Regency Library and Archives Office in implementing a social inclusion-based library transformation program”. In this study researchers used several data collection techniques: interviews, observation, documentation. The results of this study indicate that the Library and Archives Service of Siak Regency in implementing the social inclusion-based library transformation program implemented it by holding seven trainings, namely the program being: cosmetology, making bread / pastries, making chili sauce, making shredded catfish, making Sablak crackers, making traditional herbal medicine turmeric acid, making plates from palm sticks. The strategy carried out is through three stages, namely planning, implementation, and evaluation. With this training, it is hoped that it can improve the community's economy, in accordance with the initial objectives of this program.